2021
DOI: 10.1016/j.scr.2021.102239
|View full text |Cite
|
Sign up to set email alerts
|

Medical progress: Stem cells as a new therapeutic strategy for COVID-19

Abstract: Currently, the world is facing the SARS-CoV-2 pandemic, coronavirus of acute respiratory distress syndrome 2, causes of COVID-19. Coronaviruses are RNA single-stranded viruses that have an envelope. In addition, coronaviruses are classified into four subfamilies: alpha, beta, gamma and delta coronaviruses. The first of them, cause mildly symptomatic or asymptomatic infections, while beta-coronaviruses are responsible for severe diseases. SARS-CoV-2 belongs to the group of beta-coronaviruses. Current available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 79 publications
(211 reference statements)
0
5
0
1
Order By: Relevance
“…As suggested by successful MSC use in a number of pathological scenarios involving uncontrolled immune activation with consequent tissue damage, like for example H9N2 induced acute lung injury, ARDS, autoimmune diseases and graft-versus-host disease ( Waterman et al, 2010 ; Elgaz et al, 2019 ; Coelho et al, 2020 ; Yen et al, 2020 ; Barros et al, 2021 ; Musial and Gorska-Ponikowska, 2021 ; Su et al, 2021 ), the undeniable immunomodulatory and inflammation relieving properties of MSCs make them putative candidates as rejuvenating factors for the older immune system, on the basis of the documented ability to reduce pro-inflammatory mediators and to promote the expansion of regulatory lymphocyte subsets ( Yeo et al, 2021 ). Also, MSC transplantation can contribute to the amelioration of aging frailty ( Schulman et al, 2018 ; Florea et al, 2019 ; Sun et al, 2019 ), but MSC may exhibit age related deteriorating functions linked to inflammageing, especially in terms of alterations in number and characteristics of extracellular vesicles, DAMP production, excessive IL-6 release, loss of MSC ability to shift monocyte polarization toward M2, and triggering of ineffective hemopoiesis ( Tsuruhara et al, 2017 ; Lee and Yu, 2020 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
“…As suggested by successful MSC use in a number of pathological scenarios involving uncontrolled immune activation with consequent tissue damage, like for example H9N2 induced acute lung injury, ARDS, autoimmune diseases and graft-versus-host disease ( Waterman et al, 2010 ; Elgaz et al, 2019 ; Coelho et al, 2020 ; Yen et al, 2020 ; Barros et al, 2021 ; Musial and Gorska-Ponikowska, 2021 ; Su et al, 2021 ), the undeniable immunomodulatory and inflammation relieving properties of MSCs make them putative candidates as rejuvenating factors for the older immune system, on the basis of the documented ability to reduce pro-inflammatory mediators and to promote the expansion of regulatory lymphocyte subsets ( Yeo et al, 2021 ). Also, MSC transplantation can contribute to the amelioration of aging frailty ( Schulman et al, 2018 ; Florea et al, 2019 ; Sun et al, 2019 ), but MSC may exhibit age related deteriorating functions linked to inflammageing, especially in terms of alterations in number and characteristics of extracellular vesicles, DAMP production, excessive IL-6 release, loss of MSC ability to shift monocyte polarization toward M2, and triggering of ineffective hemopoiesis ( Tsuruhara et al, 2017 ; Lee and Yu, 2020 ).…”
Section: Mesenchymal Stem Cell Transplantation In Covid-19 Patients: Rationale and Resultsmentioning
confidence: 99%
“…During a cytokine storm, pro-inflammatory cytokines are secreted by the immune system, which triggers an outburst of white blood cells. As a result, suppressing the cytokine storm from eliciting acute respiratory distress syndrome (ARDS) may be one of the most important factors in COVID-19 treatment [ 31 ]. According to the literature, ECM degradation products consistently downregulate pro-inflammatory and upregulate anti-inflammatory genes and proteins, although the exact mechanisms for this ability have not been fully elucidated [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that the expression of HCV proteins during transfection of mouse cells with plasmid was accompanied by an increase in the level of proinflammatory cytokines, as well as an increase in IFN-γ in the sera of immunized mice in the case of injection of DNA alone or DNA before MSCs. The immunosuppressive effect of MSCs in this case can be compared with that observed when using MSCs for the treatment of patients with COVID-19 [ 26 ]. During the inflammatory response, many proinflammatory cytokines are secreted, including TNFα, IL-1β, IL-2, IL-6, IL-7, IL-12, IL-18, IL-33, IFN-α, and IFN-γ.…”
Section: Discussionmentioning
confidence: 99%